Black Bamboo Rhizome Extract Improves Cognitive Dysfunction by Upregulating the Expression of Hippocampal BDNF and CREB in Rats with Cerebral Ischaemia-Reperfusion Injury - Yi CA (Dove Medical Press, 2021)
Chuan-An Yi,1,* Yu-Hong Jiang,1,* Ye Wang,2 Yu-Xian Li,3 Shi-Chang Cai,4 Xiu-Yu Wu,4 Xiang-Shang Hu,4 Xing-Guang Wan4 1Medical Morphology Experimental Center, Hunan University of Medicine, Hunan, People’s Republic of China; 2Key Laboratory of Dong Medical Research Hunan Province, Hunan, People’s Republic of China; 3Department of Neurology, Hunan University of Medicine, Hunan, People’s Republic of China; 4Department of Anatomy, Hunan University of Medicine, Hunan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuan-An YiMedical Morphology Experimental Center, Hunan University of Medicine, Huaihua, 418000, Hunan Province, People’s Republic of ChinaTel +86-18674537258Email 2271604137@qq.comXing-Guang WanDepartment of Anatomy, Hunan University of Medicine, Hunan, People’s Republic of ChinaTel +86 4752382481Email 414032018@qq.comIntroduction: The study aimed to explore the effects of treatment with black bamboo rhizome extracts on learning and memory and determine the underlying mechanisms in rats with cerebral ischaemia-reperfusion injury.Methods: Sprague-Dawley rats were randomly divided into the following four groups: control, middle cerebral artery occlusion (MCAO), low-dose drug, and high-dose drug groups. Rats underwent MCAO using a suture method before drug treatment. Then, neurological impairment was assessed using the Longa scoring method, and triphenyl tetrazolium chloride staining was used to analyse the cerebral infarction area. The Elliott formula was used to calculate water content in the brain tissue. A Morris water maze (MWM) was used to assess changes in learning and memory abilities, and Western blotting was used to detect cyclic adenosine phosphate response element-binding protein (CREB) and brain-derived neurotrophic factor (BDNF) expression in the hippocampus of MCAO rats.Results: After treatment with black bamboo rhizome extracts, the neurological dysfunction score was lower in the drug groups than in the MCAO group, and a significant difference was observed between the high-dose drug and MCAO groups (P< 0.05). Additionally, the cerebral infarction area was significantly smaller in the drug groups than in the MCAO group (P< 0.01), and the effect was more obvious in the high-dose drug group than in the low-dose drug group. There was also a significant difference in water content between the high-dose drug and MCAO groups, and cerebral oedema was significantly reduced in the high-dose drug group (P< 0.05). In the MWM, the incubation period was significantly reduced, the number of platform crossings was significantly increased, and the search time was prolonged in the drug groups compared with those in the MCAO group (P< 0.05). Moreover, the expression of BDNF and CREB was significantly increased in the drug groups compared to that in the MCAO group, and the increase was more obvious in the high-dose group than in the low-dose group (P< 0.05).Discussion: Black bamboo rhizome extracts significantly improved cognitive dysfunction, reduced cerebral oedema, decreased the cerebral infarction area, and improved the neurological function score and learning and memory abilities in rats with cerebral ischaemia-reperfusion injury.Keywords: rhizome of black bamboo root, cerebral ischaemia-reperfusion injury, cognitive function, CREB/BDNF, mechanism of action